Indonesia's Imperative Steps in the Progress of Accessing into the Organisation for Economic Co-operation and Development (OECD) - Cahyaningtyas, Ivana Putri; Barus, Constantin Brilliant; Tito, Steven Dennis; Al Putra, Ferdian Ahya (Indonesian Perspective, 2025)
The Organisation for Economic Co-operation and Development (OECD) serves as an intergovernmental organization (IGO) that promotes economic and social welfare through policy coordination, norm-setting, and rule implementation. With member countries averaging a per capita income exceeding US$10,000, the OECD represents a group of high-income economies. Indonesia, currently a key OECD partner, has demonstrated strong interest in joining the organization and has undertaken various reforms to meet membership standards. However, the country faces significant challenges in aligning its sustainable development framework with OECD requirements. This study employs a qualitative-descriptive approach grounded in Institutional Liberalism theory to examine Indonesia's accession efforts. Findings indicate that while Indonesia has implemented economic improvements as part of its OECD membership plan, its middle-income status remains a major hurdle. Key obstacles include the need to boost national income, enhance international trade regulations, and strengthen infrastructure and human capital development. The research highlights that overcoming these barriers is essential for Indonesia to transition from a middle-income to a high-income economy and meet OECD membership criteria.